2014
DOI: 10.5552/drind.2014.1329
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Needs in Kitchen Design for People with Visual Impairment

Abstract: • In the modern society, about twenty percent of the population has problems with eyesight. As a result of the ageing process, it is expected that till the year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The project team developed new design concepts for kitchen lines, as well as devices for physical It has been found that there is no other publication within the available literature that presents research into the design work for kitchens produced for the elderly and people with motor impairment, which simultaneously uses traditional and environmental design methods. There are publications that refer to the design of bespoke kitchen lines for elderly and/or disabled people (e.g., [35][36][37][38][39][40][41]), but none of them consider the environmental aspects of the respective processes. On the other hand, there are publications that deal with kitchen eco-design but without any specific consideration of the needs of elderly and/or disabled people, e.g., [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The project team developed new design concepts for kitchen lines, as well as devices for physical It has been found that there is no other publication within the available literature that presents research into the design work for kitchens produced for the elderly and people with motor impairment, which simultaneously uses traditional and environmental design methods. There are publications that refer to the design of bespoke kitchen lines for elderly and/or disabled people (e.g., [35][36][37][38][39][40][41]), but none of them consider the environmental aspects of the respective processes. On the other hand, there are publications that deal with kitchen eco-design but without any specific consideration of the needs of elderly and/or disabled people, e.g., [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%